(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Stress has been found in all types of organizations especially in schools and colleges. Stress is an inevitable part of life. The good stress named as eustress is good for organizational and personal development. Many researches have been conducted to understand the level of stress among school teachers but few research have been done among college teachers. Studies have proved that teachers have moderate to high levels of stress and those working in private schools have high levels of emotional exhaustion and depersonalization. The present study has been conducted to understand the level of stress among college teachers in the self financing colleges in Tirunelveli district. Teaching problems, work overload, student problems, classroom management, participatory problems which were the factors of classroom stress. The work related stressors of these college teachers identified were fragile environment, professional development, work autonomy, transitional academics and administrative cripples. Self efficacy and role erosion of role related stress and emotional imbalance and physiological problems of health related stress are the other stressors involved in field in these self financing colleges